Pembentukan Sikap Sosial pada Pembelajaran Pendidikan Agama Islam Berwawasan Multikultural Menggunakan Pendekatan Etnografi di SMP Queen Al Falah - Ahmad Hafidh Faqihuddin; Abbas Sofwan; A. Jauhar Fuad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe the application of multicultural Islamic Religious Education (IRE) teaching methods and the mechanism of forming students' social attitudes at Queen Al Falah Junior High School. Multicultural Islamic Religious Education is an educational model that emphasizes human values, such as compassion, tolerance, mutual respect, and mutual assistance, thereby fostering harmonious social attitudes in diversity. This study uses a qualitative approach with an ethnographic type. Data were collected through observation, interviews, and documentation. The results show that multicultural Islamic Religious Education at Queen Al Falah Junior High School is implemented well. Multicultural values are integrated into student learning and guidance activities. Students' social attitudes develop through internal factors such as experience and emotions, as well as external factors such as the influence of teachers, friends, and the school environment. Multicultural values are instilled through guidance in intra- and extracurricular activities, which motivate students to appreciate tolerance, equality, justice, and democracy. Thus, multicultural-oriented PAI learning helps shape students' empathy and social attitudes amid cultural diversity